(untitled) (Annals of Medical Research, 2023)
Aim: Psychiatric disorders can cause the development of suicidal ideation. One of the disorders is called internet gaming disorder and can be influenced by the genres of the games which is played. However, there is limited information available on whether the game genres cause the development of suicidal ideation. Thus, the current study seeks to investigate the relationship between suicidal ideation and internet gaming disorder by also considering the game genres. Materials and Method: In total 1337 adolescent participants between the age range of 12-18 years were included in the study. The participants were invited to fill in the sociodemographic and online game data forms, game addiction scale-short form and children’s depression scales A comparison was made between the two groups that reported suicidal ideation and those that did not. Results: In comparison, female gender, internet gaming disorder and major depressive disorder were significant between the groups. A significant difference was found only in multiplayer online battle arena (MOBA) games among the game genres. Conclusion: Suicidal ideation is an important public problem and can lead to planning, attempting as well as completing suicide. Problematic use of internet video games in adolescents is increasing. Therefore, it can be assumed that some genres of games mediate the development of suicidal ideation.